PECULIARITIES OF TRANSFERASE ENZYMATIC ACTIVITY CHANGES IN SIMULATING ALLOXAN-INDUCED DIABETES MELLITUS IN RATS - Геруш, І.В.; Чернюх, О.Г.; Дікал, М.В. (World of Medicine and Biology, 2017)
A subject of study in this work is exploration of main biochemical indices of the blood plasma of albino rats with the background of induced diabetes mellitus (DM). Alloxan DM was modeled in rats by intraperitoneal injection of a 5% liquid of alloxan monohydrate in the dose of 150 mg/kg of body weight. On the 14th day of the experiment, the changes in the indices were compared with the control data . The results of our studies have found a pronounced hyperglycemia ranging within 11-20 mmol/L. An average glucose concentration was 12,6 ± 1,28 mmol/L that was twice as much as compared to the similar index in the group of control animals 6,0 ± 0,13 mmol/L. A significant increase in AST and GGT activity was observed, respectively, by 84% (p
Keywords: alloxan's diabetes mellitus; blood plasma; biochemical indices; albino rats